Effect of metformin on blood lipids in patients with diabetes mellitus - Haq, Tahniyah; Haq, Sabah (IMC Journal of Medical Science, 2020)
Background and objectives: Metformin improves macrovascular complications in people with diabetes mellitus (DM). Although the exact mechanism is not known, metformin has beneficial effects on dyslipidaemia. The aim of the study was to find out if there was an effect of metformin on blood lipids in people with diabetes mellitus. Method: This was a cross-sectional study which included 80 patients with diabetes mellitus. They were divided into 2 groups – (a) Group 1: on metformin and (b) Group 2: without metformin medication. None of the patients were on any other anti-diabetic medication. All data were obtained from patients’ medical records. Individual blood lipids and lipid ratios were compared between two groups. Result: Group 1 included 42 patients with a mean HbA1c of 7.58 ± 0.24% taking an average dose of 820.83 ± 60.40 mg/day of metformin. Group 2 consisted of 38 patients with mean HbA1c of 7.58 ± 0.29%. There was no significant difference in individual plasma lipid levels, lipoprotein ratio or frequency of dyslipidaemia between patients taking and not taking metformin (p>0.05). Also, different doses of metformin had no significant effect on the plasma lipid levels. Conclusion: Metformin did not affect the lipid profile of patients with diabetes mellitus. Ibrahim Med. Coll. J. 2019; 13(2): 23-27